Brand extensions’ influence on brand image : empirical study on Bodrex’sbrand - Rokhman, M. Rifqi; ., Sampurno; S., Suci Paramitasari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Bodrex’s manufacturer is attempting to use Bodrex brand success to enter flu and cough medicine category by releasing Bodrex Flu dan Batuk. The launching of Bodrex Flu dan Batuk will affect Bodrex’s brand image. The objective of this research is to examine the influence of Bodrex Flu dan Batuk on Bodrex’s brand image. This research was conducted in Yogyakarta using purposive sampling method on respondents that have been using Bodrex for 6 months. Data were collected by using questionnaire with Likert scale that measured initial brand image, category fit, image fit, consumers’ attitude towards brand extension, innovativeness, and final brand image. Structural Equation Modeling (SEM) application was used to analyse data. Research result showed that brand extension has its effect on Bodrex’s brand image, in which its final brand image was affected significantly by consumers’ attitude towards brand extension (t-value = 4.88) and initial brand image (t-value = 15.14). However, initial brand image (standardized solution = 0,88) has a larger role in final brand image formation than consumers’ attitude towards brand extension (standardized solution = 0.15). Consumers’ attitude towards Bodrex’s brand extension affected significantly by image fit (t-value = 5.29), category fit (tvalue = 1.99) and insignificantly by initial brand image (t-value = 0.49). The result also showed that innovativeness significantly (t-value = -2.79) moderates category fit relation with consumers attitude towards brand extension.Key words: brand extension, brand image, Bodrex, innovativeness